Design and Fabrication of a Fixed Bed Pyrolysis with LDPE Plastic Waste - I Made Agus Putrawan; I Ketut Gde Juli Suarbawa; I Made Rajendra; INS Winaya (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
This paper presents the design of a fixed bed reactor pyrolysis to convert plastic waste type LDPE into condensate oil. The dimensions of the batch type pyrolysis reactor are adapted to household needs and are designed to be easy to operate and transport. From the results at three different pyrolysis temperature variations; 250 oC, 275 oC and 300 oC shows that reactor yields a maximum condensate oil of 45,3wt% at temperature of 300 oC. In addition, the weight of charcoal also decreased along with the increase in operating temperature.